What topics are investigated in circular economy research? A co-word analysis using hierarchical clustering - Sánchez, José Luis Ausejo; La Rosa, Patricia Elena Ramos; Palma, Damaris Faviola Medina; Campos, Gleny Amelia Ching; Poma, Yolanda Emperatriz Maguiña (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. We analyzed the most researched topics related to the circular economy. To this end, we used a bibliometric approach, generating thematic maps that group the most used terms in the scientific literature. Design/Methodology/Approach. The present study focused on hierarchical clustering analysis to identify and understand interrelated themes in circular economy research. Adopting Ward's method, the analysis was performed without predetermining the number of groups. The data set was extracted from the Scopus database. Author keywords and keywords plus were used for the study. Results/Discussion. A hierarchical clustering analysis applied to the corpus of circular economy terms has revealed five main groups: (1) technological innovation and strategic planning, (2) adaptation and resilience in industrial processes, (3) reuse and advanced manufacturing, (4) safety and automation in the circular economy, and (5) material science and chemical sustainability. The interrelationship between the clusters identified in the analysis reflects an integrated thematic ecosystem within the circular economy, with each cluster complementing the others to address multifaceted challenges. Cluster 1, focused on the “circular economy” and “sustainable development,” is the strategic core connecting all clusters' technological and policy approaches. This cluster establishes direct links with cluster 3, where concepts such as “recycling” and “additive manufacturing” are essential to materialize the reuse strategies proposed. Cluster 2, focused on adaptation and resilience, establishes a critical connection with cluster 4 since automation and safety require adaptive models to manage dynamic processes. In addition, cluster 5, focused on sustainable materials and chemical processes, complements the objectives of cluster 1 by providing innovative solutions to improve recyclability and manage waste such as plastic waste and carbon dioxide. Conclusions. The synergies between the clusters show that progress toward a circular model depends on integrating multiple dimensions, from policy and technology strategies to advances in materials and industrial processes.